Thioether cross-linked solid polymer electrolyte membrane as well as preparation method and application thereof
The method of preparing a sulfide-crosslinked solid polymer electrolyte membrane solves the problems of poor interfacial contact of inorganic electrolytes and poor ionic conductivity of polyethylene oxide in solid lithium metal batteries. It achieves high lithium-ion conductivity and excellent mechanical properties, extends battery life, and reduces preparation costs.
Patent Information
- Application Number
- CN202610178125.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-02-08
- Publication Date
- 2026-05-05
AI Technical Summary
In existing solid-state lithium metal batteries, inorganic solid electrolytes suffer from poor interfacial contact, uneven lithium-ion transport, and high manufacturing costs, while polyethylene oxide electrolytes have poor ionic conductivity, limiting their application in solid molecular films.
A method for preparing a thioether crosslinked solid polymer electrolyte membrane was adopted. A three-dimensional thioether crosslinked network structure was formed through a thiol-epoxy click chemical reaction, which promoted the dissociation of lithium salt and reduced crystallinity, thereby improving the lithium-ion conductivity and mechanical stability.
It improves lithium-ion conductivity, reduces crystallinity, enhances polymer flexibility and mechanical stability, inhibits lithium dendrite growth, and extends battery life. Furthermore, the preparation method is simple, low-cost, and meets the requirements of green chemistry.
Smart Images

Figure CN121983662A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrolyte technology, and more specifically, to a thioether crosslinked solid polymer electrolyte membrane, its preparation method, and its application. Technical Background
[0002] Compared to traditional liquid electrolyte lithium-ion batteries, solid-state lithium metal batteries have higher energy density and better safety, making them a promising candidate for the future development of electric vehicles.
[0003] Solid-state electrolytes, as a crucial component of solid-state lithium metal batteries, significantly impact their cycle stability and lifespan. While inorganic solid-state electrolytes exhibit high ionic conductivity and excellent thermal / chemical stability, their poor interfacial contact leads to high interfacial impedance and uneven lithium-ion transport. Furthermore, the high manufacturing cost of inorganic solid-state electrolytes hinders their industrial application. In contrast, solid polymer electrolytes demonstrate superior interfacial contact due to their high flexibility and processability. Solid polymer electrolytes, particularly polyether electrolytes, have been extensively studied due to their high ether solvation capability and optimal interchain spacing.
[0004] However, the most commonly used polyethylene oxide has high crystallinity and a high melting point, resulting in poor ionic conductivity and a low cation transfer number, which hinders its practical application in solid molecular films. Summary of the Invention
[0005] In view of this,
[0006] To achieve the above objectives, the technical solution of the present invention is implemented as follows: A method for preparing a sulfide crosslinked solid polymer electrolyte membrane includes the following steps: S1. Take an appropriate amount of N,N-dimethylformamide, and then add 3,6-dioxa-1,8-octanedithiol and isonitrile triglycidyl ester respectively, and mix them evenly to obtain a mixture. S2. Add lithium bis(trifluoromethanesulfonyl)imide to the mixture, and add a magnetic stirrer to make it completely dissolve to obtain a precursor solution. S3. Pour an appropriate amount of precursor solution into a polytetrafluoroethylene mold and spread it out. Then, polymerize and crosslink it in a forced-air drying oven to form a film, thus obtaining a sulfide crosslinked network polymer electrolyte.
[0007] Further, in step S1, the molar ratio of 3,6-dioxa-1,8-octanedithiol to isonitrile triglycidyl ester is 1-3:1.
[0008] Furthermore, the mass ratio of N,N-dimethylformamide to 3,6-dioxa-1,8-octanedithiol is 25:3-1.
[0009] Further, in step S2, the molar ratio of 3,6-dioxa-1,8-octanedithiol to lithium bis(trifluoromethanesulfonyl)imide is 3:2-1.
[0010] Furthermore, in step S2, the magnetic stirring speed is 1000-1500 rpm, the temperature is 50-100 ℃, and the time is 5-7 h.
[0011] Furthermore, in step S3, the polymerization temperature is 60-80 ℃ and the polymerization time is 4-5 h.
[0012] Based on the above scheme, the second objective of the present invention is to provide a thioether crosslinked solid polymer electrolyte membrane, which is prepared by the preparation method described above. The thioether crosslinked solid polymer electrolyte membrane includes a thioether crosslinked network polymer and lithium bis(trifluoromethanesulfonyl)imide.
[0013] Furthermore, the thickness of the sulfide crosslinked solid polymer electrolyte membrane is 30-100 μm.
[0014] Based on the above-mentioned solutions, the third objective of this invention is to provide the application of sulfide crosslinked solid polymer electrolyte membranes in solid-state lithium-ion batteries.
[0015] Compared with the prior art, the present invention has the following advantages: (1) First, this invention is based on a thiol-epoxy click chemistry reaction. The sulfur atom in the thiol group of 3,6-dioxa-1,8-octanedithiol has a lone pair of electrons, which acts as a nucleophile to attack the three-membered ring of the epoxy group of isonitrileurone triglycidyl ester. The epoxy three-membered ring is opened by the nucleophile, generating a three-dimensional thioether cross-linked network structure. A large number of weakly coordinated thioether groups can promote the dissociation of lithium salt, generating a large amount of free Li. + Increase Li + The quantity of [something unclear - possibly related to molecular chains]. Secondly, the steric hindrance generated at the cross-linking points of the three-dimensional sulfide cross-linking network can hinder the orderly stacking of molecular chains, thereby significantly reducing the crystallinity of the polymer, increasing the proportion of amorphous regions, improving chain segment mobility, lowering the activation energy of chain segment movement in amorphous regions, and thus increasing ionic conductivity. Simultaneously, the weak polarity of the sulfide groups results in weaker intermolecular forces and lower frictional resistance between chain segments, making these flexible segments prone to chain segment movement. This chain segment movement not only further disrupts the regular arrangement of molecular chains and inhibits crystallization, but also drives the Li adsorbed on the chain segments through "chain segment peristalsis." +Migration occurs. Finally, the three-dimensional sulfide cross-linked network structure can also improve the mechanical stability of the polymer electrolyte, enabling it to effectively suppress the growth of lithium dendrites, prevent short circuits between the positive and negative electrodes inside the battery, and extend the service life of the lithium-ion battery.
[0016] (2) The preparation method provided by the present invention is simple to operate, has a short synthesis time, mild conditions, low cost and can be prepared on a large scale, which meets the requirements of green chemistry and is conducive to market promotion. Attached Figure Description
[0017] To more clearly illustrate the technical solutions in this invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0018] Figure 1 Figure a shows a physical image (Figure a) and a flexibility test image (Figure b) of the thioether crosslinked solid polymer electrolyte membrane described in Example 1 of the present invention. Figure 2 This is a diagram illustrating the synthesis mechanism of the thioether crosslinked solid polymer electrolyte membrane described in Example 1 of the present invention; Figure 3 The FITR spectrum (Figure a) and X-ray diffraction pattern (Figure b) of the sulfide crosslinked solid polymer electrolyte membrane described in Example 1 of the present invention are shown. Figure 4 The images show the DSC diagram (Figure a) and tensile property comparison diagram (Figure b) of the thioether crosslinked solid polymer electrolyte membrane described in Example 1 of the present invention. Figure 5 The electrochemical impedance spectroscopy (EIS) diagram (Figure a) and ion transport number (it) diagram (Figure b) of the thioether crosslinked solid polymer electrolyte membrane described in Example 1 of the present invention at room temperature are shown. Figure 6 The lithium-ion symmetric battery assembled from the sulfide-crosslinked solid polymer electrolyte membrane and lithium sheet described in Example 1 of this invention operates at 0.1 mA cm⁻¹. -2 and 0.1mAcm -2 Performance graph under long-cycle conditions. Detailed Implementation
[0019] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings.
[0020] It should be noted that, in the description of the embodiments of this application, the term "some specific embodiments" means that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same implementation or instance. Moreover, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0021] In this embodiment, "within the range" includes the values at both ends, such as "within the range of 1 to 100", which includes the values at both ends of 1 and 100.
[0022] This invention provides a method for preparing a thioether crosslinked solid polymer electrolyte membrane, comprising the following steps: S1. Take an appropriate amount of N,N-dimethylformamide, and then add 3,6-dioxa-1,8-octanedithiol and isonitrile triglycidyl ester respectively, and mix them evenly to obtain a mixture. S2. Add lithium bis(trifluoromethanesulfonyl)imide to the mixture, and add a magnetic stirrer to make it completely dissolve to obtain a precursor solution. S3. Pour an appropriate amount of precursor solution into a polytetrafluoroethylene mold and spread it out. Then, polymerize and crosslink it in a forced-air drying oven to form a film, thus obtaining a sulfide crosslinked network polymer electrolyte.
[0023] Therefore, this invention proposes a method for preparing thioether crosslinked network polymers using a simple click chemistry approach, and for preparing weakly coordinated thioether crosslinked network solid lithium-ion polymer electrolytes. This invention uses a crosslinking agent with multi-arm epoxy groups, which facilitates the formation of a thioether crosslinked network structure, reduces the crystallinity of the solid polymer electrolyte, promotes polymer chain movement, and improves lithium-ion conductivity. The thioether group and Li... + It has a relatively weak coordination effect, promoting the dissociation of lithium salts, making Li... + It is easier to dissociate from the coordination sites, increasing the number of lithium ions. Cross-linked network solid polymers also provide excellent mechanical properties, which can effectively suppress the growth of lithium dendrites and extend the life of lithium-ion batteries.
[0024] Specifically, in step S1, the molar ratio of 3,6-dioxa-1,8-octanedithiol to triglycidyl isocyanate is 1-3:1, and the mass ratio of N,N-dimethylformamide to 3,6-dioxa-1,8-octanedithiol is 25:3-1.
[0025] That is, dissolve 0.2-0.5 g of 3,6-dioxa-1,8-octanedithiol in 10-30 mL of N,N-dimethylformamide, mix well, and then add 0.4-1 g of triglycidyl isonitrile and mix well.
[0026] Specifically, in step S2, the molar ratio of 3,6-dioxa-1,8-octanedithiol to lithium bis(trifluoromethylsulfonyl)imide is 3:2-1, the magnetic stirring speed is 1000-1500 rpm, and the time is 5-7 h, so that the precursor solution is completely dissolved.
[0027] A suitable amount of precursor solution is poured into a polytetrafluoroethylene mold and spread evenly. The mixture is then polymerized and crosslinked in a forced-air drying oven to form a film, thus obtaining a sulfide crosslinked network polymer electrolyte. Specifically, in step S3, the polymerization conditions for the sulfide crosslinked network polymer electrolyte are: polymerization temperature 60-80 ℃ and polymerization time 4-5 h.
[0028] The preparation method provided by this invention is simple to operate, has a short synthesis time, mild conditions, low cost, and can be prepared on a large scale. It meets the requirements of green chemistry and is conducive to market promotion.
[0029] Based on the above scheme, another embodiment of the present invention provides a coordination sulfide crosslinked network type solid polymer electrolyte, which is prepared by the above preparation method. The sulfide crosslinked solid polymer electrolyte membrane includes a sulfide crosslinked network polymer and lithium bis(trifluoromethanesulfonyl)imide.
[0030] The thickness of the sulfide crosslinked solid polymer electrolyte membrane is 30-100 μm.
[0031] The weak coordination of thioether groups in thioether-crosslinked solid polymer electrolyte membranes with high lithium-ion conductivity can promote the dissociation of lithium salts, generating a large amount of free Li. + Thioether cross-linked network polymers help reduce polymer crystallinity, improve chain segment mobility, and lower the activation energy of chain segment movement in amorphous regions, thus increasing ionic conductivity. Finally, cross-linked network solid polymers also provide excellent mechanical properties, enabling them to effectively suppress lithium dendrite growth and extend the lifespan of lithium-ion batteries.
[0032] Based on the above solution, another embodiment of the present invention provides the application of sulfide crosslinked solid polymer electrolyte membrane in solid lithium-ion batteries.
[0033] This invention utilizes the properties of thioether cross-linked network polymers. The weak coordination of the thioether groups is beneficial to the dissociation of lithium salts. The thioether cross-linked network structure can reduce the crystallinity of solid polymer electrolytes, promote the movement of polymer chain segments, and improve lithium-ion conductivity, resulting in better electrochemical performance of solid lithium-ion batteries.
[0034] Based on the above embodiments, the present invention provides the following specific examples to further illustrate the invention. It should be understood that these examples are for illustrative purposes only and are not intended to limit the scope of the invention. Experimental methods in the following examples, unless otherwise specified, are generally performed according to the manufacturer's recommended conditions. Unless otherwise stated, percentages and parts are calculated by mass.
[0035] Example 1 This embodiment provides a method for preparing a sulfide crosslinked solid polymer electrolyte membrane, including the following steps: (1) Use a pipette to transfer 20 mL of N,N-dimethylformamide into a glass bottle, and then weigh 0.75 g of 3,6-dioxa-1,8-octanedithiol and 0.8172 g of isonitrile triglycidyl ester. Use a magnetic stirrer to mix the solution thoroughly.
[0036] (2) After mixing evenly, add 0.4074 g of lithium bis(trifluoromethylsulfonyl)imide to a glass bottle, add a magnetic stir bar and place it on a magnetic stirrer to dissolve it completely to obtain a precursor solution.
[0037] (3) Pour 10 ml of the precursor solution into a polytetrafluoroethylene mold with a diameter of 10 cm. Place it in a drying oven at 80 °C for crosslinking polymerization for 4 h to obtain a sulfide crosslinked solid polymer electrolyte membrane.
[0038] Taking the sulfide-crosslinked solid polymer electrolyte membrane prepared in Example 1 as an example, its morphology and structure were characterized to obtain... Figure 1-6 The results are shown in the figure.
[0039] Figure 1 Figure a shows a physical image of the solid polymer electrolyte (Figure a) and a diagram of its flexibility test (Figure b). Figure 1 As can be seen from 'a', the solid polymer electrolyte is transparent and smooth with a flat and dense surface, indicating that it can make close contact with the positive and negative electrodes, reducing interfacial resistance. Simultaneously, its low crystallinity is beneficial for improving lithium-ion conductivity. From... Figure 1 As can be seen from b, solid polymer electrolytes have excellent flexibility and mechanical properties, and can be repeatedly bent and folded, which is beneficial for suppressing the growth of lithium dendrites.
[0040] Figure 2This is a schematic diagram illustrating the synthesis mechanism of the thioether crosslinked solid polymer electrolyte membrane described in Example 1 of this invention. The S atom in the thiol group of 3,6-dioxa-1,8-octanedithiol possesses a lone pair of electrons, which acts as a nucleophile to attack the three-membered ring of the isocyanuric acid triglycidyl ester epoxy group. The epoxy three-membered ring is opened by the nucleophile, generating a three-dimensional thioether crosslinked network structure.
[0041] Figure 3 The images show the FITR spectrum (Figure a) and X-ray diffraction pattern (Figure b) of the thioether crosslinked solid polymer electrolyte membrane described in Example 1 of this invention. Figure a shows that the solid polymer electrolyte membrane exhibits a region located at 1685 cm⁻¹. -1 The characteristic C=O infrared peak indicates that the polymer electrolyte was polymerized using triglycidyl isocyanate as a crosslinking agent, located at 3445 cm⁻¹. -1 The -OH infrared characteristic peak appears, located at 2550 cm⁻¹. -1 The disappearance of the -SH infrared characteristic peak indicates that the thiol group and epoxy group undergo a ring-opening reaction to form -OH. Figure b shows that the solid polymer electrolyte exhibits a broad diffraction peak between 15° and 25°, indicating that it is favorable for Li... + Migrating amorphous state.
[0042] Figure 4 Figure a shows the DSC diagram (Figure a) and tensile property diagram (Figure b) of the sulfide crosslinked solid polymer electrolyte membrane described in Example 1 of this invention. Figure a shows that the glass transition temperature of the solid polymer electrolyte is -67.2℃. Figure b shows that the polymer electrolyte membrane has good tensile strength and strong mechanical stability.
[0043] Figure 5 The figures show the electrochemical impedance spectroscopy (EIS) spectrum (Figure a) and ion transport number (it) spectrum (Figure b) of the thioether crosslinked solid polymer electrolyte membrane described in Example 1 of this invention at room temperature. Figure a shows that the bulk resistance of the polymer electrolyte is 11 Ω, and the ionic conductivity of the polymer electrolyte is calculated to be 5.7 × 10⁻⁶ Ω using the ionic conductivity formula. -4 S cm -1 The lithium-ion transference number calculated from Figure b using the formula is 0.75.
[0044] Figure 6 The lithium-ion symmetric battery assembled from the sulfide-crosslinked solid polymer electrolyte membrane and lithium sheet described in Example 1 of this invention operates at 0.1 mA cm⁻¹. -2 and 0.1mA cm -2 Long-term cycling performance under certain conditions. The lithium-symmetric battery assembled with a solid polymer electrolyte exhibits cycling performance exceeding 1000 hours and has a low polarization voltage.
[0045] The above electrochemical tests demonstrate that the thioether crosslinked solid polymer electrolyte membrane possesses excellent mechanical stability and electrochemical performance.
[0046] Example 2 This embodiment provides a method for preparing a thioether crosslinked solid polymer electrolyte membrane, which differs from Example 1 in that: In step 1), 0.8295 g of 3,6-dioxa-1,8-octanedithiol was weighed; the remaining steps and parameters were the same as in Example 1.
[0047] Electrochemical tests were performed on the sulfide-crosslinked solid polymer electrolyte membrane prepared in Example 2. The sulfide-crosslinked solid polymer electrolyte membrane achieved an ionic conductivity of 3 × 10⁻⁶ at room temperature. -4 S cm -1 The lithium-ion transference number is 0.6, and the cycle life of the lithium symmetric battery is 900 h.
[0048] Example 3 This embodiment provides a method for preparing a thioether crosslinked solid polymer electrolyte membrane, which differs from Example 1 in that: In step 1), 0.5925 g of 3,6-dioxa-1,8-octanedithiol was weighed; the remaining steps and parameters were the same as in Example 1.
[0049] Electrochemical tests were performed on the sulfide-crosslinked solid polymer electrolyte membrane prepared in Example 3. The sulfide-crosslinked solid polymer electrolyte membrane achieved an ionic conductivity of 4 × 10⁻⁶ at room temperature. -4 S cm -1 The lithium-ion transference number is 0.58, and the cycle performance of the lithium symmetric battery is 800 h.
[0050] Comparative Example 1 The difference from Example 1 is as follows: In step 1), 0.337 g of 1,3-dioxolane was weighed; the remaining steps and parameters were the same as in Example 1.
[0051] Electrochemical tests were performed on the ether-oxygen crosslinked network solid polymer electrolyte prepared in Comparative Example 1. The ionic conductivity of the ether-oxygen crosslinked network solid polymer electrolyte reached 1.25 × 10⁻⁶ at room temperature. -6 S cm -1 The lithium-ion transference number is 0.32, and the cycle performance of the lithium symmetric battery is 400 h.
[0052] Comparative Example 2 The difference from Example 1 is as follows: In step 1), 0.241 g of 1,3-dioxolane was weighed; the remaining steps and parameters were the same as in Example 1.
[0053] Electrochemical tests were performed on the ether-oxygen crosslinked network solid polymer electrolyte prepared in Comparative Example 2. The ionic conductivity of the ether-oxygen crosslinked network solid polymer electrolyte reached 2.15 × 10⁻⁶ at room temperature. -6 S cm -1 The lithium-ion transference number is 0.4, and the cycle performance of the lithium symmetric battery is 200 h.
[0054] As can be seen from the above embodiments, the thioether crosslinked solid polymer electrolyte membrane provided by the present invention has good interfacial stability and excellent electrochemical performance.
[0055] While the present invention has been disclosed above, its scope of protection is not limited thereto. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention, and all such changes and modifications will fall within the scope of protection of the present invention.
Claims
1. A method for preparing a sulfide-crosslinked solid polymer electrolyte membrane, characterized in that, Includes the following steps: S1. Take N,N-dimethylformamide, and then add 3,6-dioxa-1,8-octanedithiol and isonitrile triglycidyl ester, respectively, and mix them evenly to obtain a mixture. S2. Add lithium bis(trifluoromethanesulfonyl)imide to the mixture and stir until it is completely dissolved to obtain a precursor solution. S3. Pour an appropriate amount of precursor solution into a polytetrafluoroethylene mold and spread it out. Then, polymerize and crosslink it in a forced-air drying oven to form a film, thus obtaining a solid polymer electrolyte membrane.
2. The preparation method according to claim 1, characterized in that, In step S1, the molar ratio of 3,6-dioxa-1,8-octanedithiol to triglycidyl isocyanate is 1-3:
1.
3. The preparation method according to claim 1, characterized in that, The mass ratio of N,N-dimethylformamide to 3,6-dioxa-1,8-octanedithiol is 25:3-1.
4. The preparation method according to claim 1, characterized in that, In step S2, the molar ratio of 3,6-dioxa-1,8-octanedithiol to lithium bis(trifluoromethylsulfonyl)imide is 3:2-1.
5. The preparation method according to claim 3, characterized in that, In step S2, magnetic stirring is used, with a stirring speed of 1000-1500 rpm, a temperature of 50-100 ℃, and a stirring time of 5-7 h.
6. The preparation method according to claim 1, characterized in that, In step S3, the polymerization temperature is 60-80 ℃ and the polymerization time is 4-5 h.
7. A sulfide-crosslinked solid polymer electrolyte membrane, characterized in that, It is prepared by the preparation method according to any one of claims 1-6.
8. The sulfide crosslinked solid polymer electrolyte membrane according to claim 7, characterized in that, The thickness of the thioether crosslinked solid polymer electrolyte membrane is 30-100 μm.
9. The application of the sulfide crosslinked solid polymer electrolyte membrane as described in claim 7 or 8 in solid-state lithium-ion batteries.
Citation Information
Cited By
Composite polymer electrolyte for energy storage frequency modulation lithium-sulfur battery and preparation method and application thereof
CN122267297A